Effect of freezing on polyphenol levels and antioxidant capacity of the fruit pulp of Syzygium paniculatum (eugenio) - López-Marín, Beatriz Estella; Noguera-Córdoba, Diego Fernando; Aragón-Rincón, Julián Camilo (Revista Colombiana de Investigaciones Agroindustriales, 2024)
Syzygium paniculatum, or eugenio, is a tree used for ornamental purposes. It produces an edible fruit characterized by its polyphenol content and high antioxidant capacity, yet it remains relatively unknown in the community and many of its fruits go to waste. One alternative to encourage its consumption is freezing. This study aimed to evaluate the effect of freezing on the levels of polyphenols and antioxidant capacity of S. paniculatum fruit. The fruits were collected in Medellín and Granada, Colombia. Subsequently, the pulp was obtained and subjected to freezing at -20 °C. Polyphenol content was assessed using the Folin-Ciocalteu method, and antioxidant capacity was measured using the ORAC-H (Oxygen Radical Absorbance Capacity hydrophilic) technique. Measurements were taken before freezing (baseline), and at 15 and 45 days post-freezing. The measurement of polyphenols revealed a baseline with an average of 826 ± 6.95 mg GAE/100 g sample (N = 6). After freezing, a decrease in polyphenol concentration was observed at both 15 and 45 days. Regarding antioxidant capacity, the initial ORAC-H value in the fresh pulp was 935 ± 7.04 μmol TE/100 g sample. During storage, there were no significant changes in antioxidant capacity between day 0 and 45. By confirming that a significant antioxidant capacity is maintained even after a freezing process, eugenio can be considered as a food with potential immunomodulatory properties and importance in cancer prevention.